Mathematics Instruction to Promote Mathematics Higher-Order Thinking Skills of Students in Indonesia: Moving Forward - Benidiktus Tanujaya (UIKTEN, 2021)
HOTS instruction in mathematics is rarely explicitly programmed by the schoolteacher. As a result, students' HOTS is at the lowest level, especially in national or international assessments. The purpose of this research is to determine why mathematics education in Indonesia does not have a significant effect on student HOTS by conducting a review of several Indonesian publications on the subject. This research is a qualitative method of literature review related to the HOTS of Indonesian mathematics students, and an organized interview triangulated to support the data and information from the literature review. The interview consisted of two critical questions administered using Google Form: implementing active learning and mathematics textbooks on mathematics classroom activities. The results concluded that there were two primary sources of error in mathematics learning to increase HOTS in Indonesia: active learning and current mathematics textbooks. Besides, in teaching and learning practices, the active learning model is rarely used when using official texts that do not promote HOTS for mathematics students in Indonesia.